ISLAMIC WORK ETHIC & ORGANIZATIONAL COMMITMENT GURU DAN KARYAWAN MADRASAH ALIYAH SWASTA DI KOTA MALANG - Zaim Mukaffi., Siswanto (El-QUDWAH, 2013)
ISLAMIC WORK ETHIC ORGANIZATIONAL COMMITMENT GURU DAN KARYAWAN MADRASAH ALIYAH SWASTA DI KOTA MALANG   Oleh: Siswanto Zaim Mukaffi Dosen Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang   Abstract The purpose of this study is to analyze the implementation Islamic work ethic and organizational commitment of employee’s private Islamic higher education school based on biographical characteristics. Biographical characteristics are consists of age, gender, marital status, number of children, education level, education, and salary. Total sample in the research are 70 respondents. Data analysis is executed by independent samples t-test and Analysis of Varians (Anova). Based on the research indicate that employee organization commitment is quitely different between men and women.  The implementation of Islamic work ethic based on marital status is quietly different in higher level of significant. Managerial implications of human resource management requires to enhance an organizational commitment of private Islamic higher education school women employees. Keyterm: Islamic Work Ethic, Organizational Commitment, Islamic School